Quality of life among health care workers in Arab countries 2 years after COVID-19 pandemic - Ghazy, Ramy Mohamed; Abubakar Fiidow, Osman; Abdullah, Fatimah Saed Alabd; Elbarazi, Iffat; Ismail, Ismail Ibrahim; Alqutub, Sulafa Tarek; Bouraad, Etwal; Hammouda, Esraa Abdellatif; Tahoun, Mohamed Mostafa; Mehdad, Silmane; Ashmawy, Rasha; Zamzam, Abdulla; et al. (Frontiers in Public Health, 2022)
Background: Assessment of the quality of life (QoL) among healthcare workers (HCWs) is vital for better health care and is an essential indicator for competent health service delivery. Since the coronavirus disease 2019 (COVID-19) pandemic strike, HCWs became in the frontline position, subjecting them to tremendous mental and psychological burden with a high risk of virus acquisition. Aim: This study evaluated the QoL and its influencing characteristics among HCWs residing in Arabic countries. Methods: This was a cross-sectional study using self-administered online survey based on the World Health Organization QoL survey instrument with additional questions added on COVID-19 distributed in three different languages (Arabic, English and French) in 19 Arab countries between 22 Feb and 24 March 2022. Results: Around 3170 HCWs residing in 19 Arab countries responded to the survey. Majority are females (75.3%), 18-40 years of age (76.4%), urban residents (90.4%), married (54.5%), and lived in middle-income countries (72.0%). The mean score of general health and general QoL are 3.7±1.0 and 3.7±0.9, respectively. Those who attained average physical, psychological, social, and environmental QoL are 40.8%, 15.4%, 26.2%, and 22.3%, respectively. The income per capita and country income affected the mean score of all domains of QoL. Previous COVID-19 infection, having relatives who died of COVID-19 and being vaccinated against COVID-19 significantly affected the mean score of different domains. Conclusion: A large proportion of the Arab HCWs had an overall poor QL. More attention should be directed to this vulnerable group to ensure their productivity and service provision.